Educational activity of Sergey Rayevsky as factor of sociocultural dynamics of slobozhansky moderny society: cultural and philosophical contents - Фрадкіна, Н. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2017)
The forgotten figure of the outstanding educator of Slobozhanshchina of the XIX century S. A. Rayevsky is covered in article. The philosophical its comprehensive culture creative activity, which shows us an example of disinterested service to the people of the real intellectual is comprehended. It is noted that use of educational potential of the identity of Sergey Rayevsky allows to speak about link of times and education of new ethics of the Ukrainian intellectual elite.